KEABSAHAN TANDA TANGAN ELEKTRONIK PADA AKTA NOTARIS - Jenny Divia Fitcanisa; Busyra Azheri (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
The development of information and electronic technology, which is currently increasing rapidly, has an impact on the Notary's work related to the signing of the Notary deed. The cyber notary concept contained in Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary (hereinafter referred to as UUJN) in the elucidation of Article 15 paragraph (3) states that there are other powers for a Notary, namely the authority to certify transactions carried out electronically (cyber notary) but in the absence of regulations regarding this matter it seems to be an obstacle to the implementation of electronic signing. Based on this, the authors formulate the problem, namely, first how to regulate norms regarding electronic signatures on notarial deeds, Second, how are the requirements for an electronic signature on a notary deed to be considered legally valid. This study uses a juridical-normative approach. The results of this research study indicate that the regulation of Cyber notary has not been regulated in Indonesia so because there is no regulation regarding the electronic signing of the notary deed, the notary cannot carry out the signing of the deed electronically under any circumstances. The legal requirements relating to the electronic signature do not meet the requirements for a valid signature on a notary deed because according to Article 16 UUJN it requires the signature to be carried out directly by the appearer or the parties before the notary.